(untitled) (Global Journal of Science Frontier Research, 2020)
This research aimed to evaluate the adsorption process of cyanide ion (CN -) contained in synthetic aqueous solution, using activated carbon obtained from coffee residue, studying its efficiency and equilibrium and kinetic models. Activated carbon was characterized by Fourier Transform infrared analysis (FTIR), X-ray diffraction (DRX), and iodine number determination. A central composite design (CCD) with three factors adapted to three levels each and six central points was applied to study the effect of pH (A), contact time (B) and adsorbent dosage (C); According to the analysis of variance, the factors A, B, C, and the square AA were significant in the adsorption efficiency of cyanide onto activated carbon, whose maximum value reached was 54.68% and 67.65% for the predictive level. According to the coefficient of determination (R 2 ), Freundlich’s isothermal model (0.954) and the three kinetic equations of pseudo-second order (0.991, 0.993, 0.993) fit the experimental process. From the results obtained, the active carbon prepared from coffee residue can be used as a potential adsorbent of CN -, contained in aqueous solutions of low concentrations.